The prevalence and factors associated with posttraumatic growth after 3-years outbreak of COVID-19 among resident physicians in China: a cross-sectional study - Zeng, Zixuan; Wang, Huan; Zhou, Yaxing; Lu, Zhanghong; Ci, Renyangcuo; Lin, Yezhe; Zeng, Xiaoping; Huang, Lei (Frontiers in Psychiatry, 2023)
The Coronavirus disease 2019 (COVID-19) pandemic is a global traumatic event that has profoundly struck individuals’ mental health. However, this might potentially promote positive transformation such as posttraumatic growth (PTG). Studies have indicated that the COVID-19 pandemic negatively affected the well-being of resident physicians, but little is known about PTG among this vulnerable population in China. Therefore, this study investigated the prevalence and associated factors of PTG among Chinese resident physicians after 3-years outbreak of COVID-19. In total, 2267 Chinese resident physicians completed an online survey from 9 March to 20 March in 2023. PTG was assessed using the 10-item Posttraumatic Growth Inventory-Short Form (PTGI-SF). Scores ≥30 implied moderate-to-high PTG. We also collected possible associated factors for PTG, including socio-demographic and psychological variables. We analyzed the data by applying descriptive statistics, univariable and multivariable logistic regression models. Results indicated that 38.7% of the resident physicians reported moderate-to-high PTG. In the multivariable logistic regression models, age (odds ratio, OR=1.039; 95% confidence interval, 95%CI=1.008-1.070), female (OR=1.383, 95%CI=1.151-1.662), satisfied or neutral with annual income (OR=2.078, 95%CI=1.524-2.832; OR=1.416, 95%CI=1.157-1.732), sufficient support at work (OR=1.432, 95%CI=1.171-1.751) and resilience (OR=1.171, 95%CI=1.096-1.252) were significantly positively associated with moderate-to-high PTG. On the contrary, burnout (OR=0.653, 95%CI=0.525-0.812), depression symptoms (OR=0.700, 95%CI=0.552-0.889), and stress (OR=0.757, 95%CI=0.604-0.949) were significantly negatively associated with moderate-to-high PTG. Overall, resident physicians in China experienced relatively high prevalence of PTG that could be associated with several psychosocial factors. Findings may provide evidence to develop interventions for resident physicians to systematically and constructively process traumatic events related to the pandemic and foster their PTG.